Sedimentology and stratigraphic evolution of a tidally influenced marginal-marine complex: The Lower Cretaceous McMurray Formation, Athabasca oil sands deposit, northeastern Alberta - Crerar, Erin Elizabeth (University of Ottawa (Canada), 2003)
Within the Lewis study area, McMurray Formation strata comprise 4 facies associations that form a depositional continuum of braided-fluvial (FA1), tidally-influenced braided- to low-accommodation meandering-fluvial and meandering-tidal channel-fills (FA2), associated overbank (FA3), and open-estuarine tidal flat deposits (FA4). The primary reservoir occurs in transgressive FA2 deposits. Lower-FA2 channels incise older water-wet FA1sand and consist of medium to locally-coarse, bitumen-saturated sand with rare to locally common pin-stripe laminated and/or 1--5 cm thick mud beds. Channels were initially confined by steep valley walls formed along the sub-Cretaceous unconformity. As a consequence, coeval interchannel sediment (FA3) was cannibalized by lateral channel migration and occurs only as common mud-clasts. The net result was the accumulation of a sand-rich, sheet-like deposit with locally-preserved fine-grained interchannel deposits, suggesting a high rate of lateral versus vertical accretion. With the filling and elimination of the irregular paleotopography along the unconformity, upper-FA2 channels became unconfined and formed thick, areally extensive inclined heterolithic stratification (IHS) deposits. Similarly, coeval interchannel deposits are more widely-distributed and thickly preserved compared to underlying strata. (Abstract shortened by UMI.)
Keywords: Geology.